2021
DOI: 10.3390/ijerph18030912
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Intention to Adopt Blockchain Food Traceability Technology towards Organic Food Products

Abstract: Establishing a blockchain food traceability system (BFTS) is increasingly important and urgent to resolve the contradiction between consumers’ intention regarding safe food selections and the spread of polluted foods. Using the advantages of blockchain, such as immutability, decentralization, openness, and anonymity, we can build trusted food traceability systems based on these important characteristics. With reliable information, traceability from production to sales can effectively improve food safety. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 75 publications
5
56
1
2
Order By: Relevance
“…First, the intention of consumers to switch services between dissimilar learning platforms can be seen as an immigration behavior (Lin and Wu, 2021 ; Lin et al, 2021 ). Second, former studies have confirmed the effectiveness of PPM to explain and interpret switch intention in various immigration scenarios, that is, blogger activities (Chang et al, 2014 ), network games (Hou et al, 2011 ), mobile medical platforms (Hwang et al, 2015 ), mobile messaging applications (Liao et al, 2019 ), and mobile services (Calvo-Porral and Levy-Mangin, 2015 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the intention of consumers to switch services between dissimilar learning platforms can be seen as an immigration behavior (Lin and Wu, 2021 ; Lin et al, 2021 ). Second, former studies have confirmed the effectiveness of PPM to explain and interpret switch intention in various immigration scenarios, that is, blogger activities (Chang et al, 2014 ), network games (Hou et al, 2011 ), mobile medical platforms (Hwang et al, 2015 ), mobile messaging applications (Liao et al, 2019 ), and mobile services (Calvo-Porral and Levy-Mangin, 2015 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Trust is an experience feeling and experience of cultural background and psychological formation of a person (Lee and Turban, 2001 ). Consumers who are more trusting may prefer to choose a trustworthy remote service platform rather than lose a precious opportunity (Lin et al, 2021 ). Therefore, we believe that improving the fidelity of simulation (the accuracy of replication), especially breaking through the cost limit of medical distance learning, the limit of engineering technology, avoiding danger, ethics, psychological measurement requirements, and time limit, and improving the elements of trust are likely to increase users intention to use medical telelearning platform, thus affecting the sustainability of mobile education platform use, more active and effective response to the outbreak of COVID-19.…”
Section: Research Modelmentioning
confidence: 99%
“…Examining the relation between BCT and various industries may aid in understanding the significance of these technologies, particularly in light of the COVID-19 outbreak. According to our findings, the food and agricultural sector has the most commonly utilized BCT, with 19 articles addressing COVID-19 conditions [5,56,57,66,71,79,82,83,85,87,89,94,100,101,103,106,109,110,114]. With 12 research papers since the outbreak, the healthcare industry has made a significant contribution to the reviewed articles.…”
Section: Industry Sectorsmentioning
confidence: 86%
“…Table 2 The findings indicate that, of all the BCT categories, digitalization had the highest frequency in the reviewed studies, with 22 articles out of 72 [3,13,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. With ten articles, visibility was also one of the most common BCT [5,20,[77][78][79][80][81][82][83][84]. Sixteen of the papers looked at the impact of both digitization and visibility on the SC and the COVID-19 pandemic simultaneously [5,23,[85][86][87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Blockchain Technologiesmentioning
confidence: 98%
“…These are in line with the work in [ 10 ] which concludes that the use of blockchain technology can improve sustainability from social, environmental, and market perspective. In [ 11 , 12 , 13 , 14 ], blockchain tools are referred to as possibly the most appropriate to meet the requirements of the rapidly expanding food value chains such as traceability, auditability, fault tolerance, and flexibility. Research on certification using blockchain [ 15 ] has also evolved with many interesting sustainability efforts.…”
Section: Related Workmentioning
confidence: 99%